Fuzzy Based Particle Swarm Optimization for Modeling Home Appliances towards Energy Saving and Cost Reduction under Demand Response Consideration - Parvin K.; Hannan M.A.; Al-Shetwi A.Q.; Ker P.J.; Roslan M.F.; Mahlia T.M.I. (Institute of Electrical and Electronics Engineers Inc., 2023)
Air conditioning; Constrained optimization; Controllers; Cost benefit analysis; Cost reduction; Electric power utilization; Energy efficiency; Energy management systems; Energy utilization; Fuzzy logic; Gas emissions; Greenhouse gases; Heating; HVAC; Lighting; Membership functions; Particle swarm optimization (PSO); Solar buildings; Traffic signals; Water heaters; Electric water heaters; Energy consumption and cost; Fuzzy logic controllers; Heating ventilation and air conditioning; Optimal performance; Optimized controllers; Sustainable energy; Sustainable environment; Domestic appliances